LeadershipRolesandFunctionsofTheFarmer Batang Bunai inVillage Pisang Berebus District of Gunung ToarRegency KuantanSingingiRiauProvince - Yulina, Yunar; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This studywas conducted inDecember 2012inthe village Pisang Berebusdistricts ofGunung Toar RegencyKuantanSingingiRiauProvince. The method usedin this studyisasurveymethod. Respondentconductedthe census. Respondentsin thestudywerefarmers,Oreochromis andPangasius sp, amounting to 15people.The purposeof this study were1) Knowingthe roleof leadershipinfarmers'groupfishfarming inthe villagePisang Berebus, 2) Knowingthe function ofleadershipgroupsoffish in the village Pisang Berebus.The resultsoftheseresearchesshow thatthe roleandfunction ofleadership offarmer groupsBatang Bunai in the village Pisang Berebus using thefrequenciesinquestionareexpressedqualitatively ieVeryGood,Good,less Good, No Good, Very NotGood.Furthermathematicalcalculationshowed that theleadershiproleof fishfarmer groups in the villagePisang Berebus areinthe category of "Good"thoughtful, responsible, andfairwith a totalof399scores, andthe function ofleadershipis inthe category of "Good"canguide themembersofthe groupina business carried onwith a totalscore1204. Decreased production offishinthevillage ofPisangBerebuswere not causedby a decrease inLeadershipRolesand Functions ofthegroupbutbecause of the highproduction costsof fishfarming.Keyword :Role, function, leader,farmer groups